The 2019 Conference on Artificial Life 2019
DOI: 10.1162/isal_a_00207
|View full text |Cite
|
Sign up to set email alerts
|

When is an action caused from within? Quantifying the causal chain leading to actions in simulated agents

Abstract: An agent's actions can be influenced by external factors through the inputs it receives from the environment, as well as internal factors, such as memories or intrinsic preferences. The extent to which an agent's actions are "caused from within", as opposed to being externally driven, should depend on its sensor capacity as well as environmental demands for memory and context-dependent behavior. Here, we test this hypothesis using simulated agents ("animats"), equipped with small adaptive Markov Brains (MB) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…What is the difference between a mechanism and decisionmaking (choice)? This has been widely discussed in the philosophy literature (Barandiaran and Moreno, 2006;Haig and Dennett, 2017) and is now becoming an important issue for bench biologists working in basal cognition of somatic cells and synthetic biology (Perkins and Swain, 2009;Balazsi et al, 2011;Reid et al, 2013Reid et al, , 2016Mitchell and Lim, 2016;Paul et al, 2016;Vesty et al, 2016;Bugaj et al, 2017) as well as for workers in artificial life (Juel et al, 2019). Without attempting to deal with this profound question in full, it can be mentioned that the perspective taken herein suggests that several factors contribute to a smooth transition between biochemical mechanism and agency: integration of remote events into the causal chain (spatial distance, and temporal distance -memory/ anticipation), and stochasticity (distance in terms of predictive capability).…”
Section: Box | Continuedmentioning
confidence: 99%
“…What is the difference between a mechanism and decisionmaking (choice)? This has been widely discussed in the philosophy literature (Barandiaran and Moreno, 2006;Haig and Dennett, 2017) and is now becoming an important issue for bench biologists working in basal cognition of somatic cells and synthetic biology (Perkins and Swain, 2009;Balazsi et al, 2011;Reid et al, 2013Reid et al, , 2016Mitchell and Lim, 2016;Paul et al, 2016;Vesty et al, 2016;Bugaj et al, 2017) as well as for workers in artificial life (Juel et al, 2019). Without attempting to deal with this profound question in full, it can be mentioned that the perspective taken herein suggests that several factors contribute to a smooth transition between biochemical mechanism and agency: integration of remote events into the causal chain (spatial distance, and temporal distance -memory/ anticipation), and stochasticity (distance in terms of predictive capability).…”
Section: Box | Continuedmentioning
confidence: 99%
“…This is demonstrated particularly well by recent computational studies involving simulated artificial agents with minimal cognitive architectures [ 15 , 23 , 68 , 69 ], whose behavior can easily be predicted. Yet, understanding what caused the agent to perform a particular action typically requires extensive additional analysis and cannot be addressed in purely reductionist or holistic terms [ 31 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the relation between surprisal, Φ and the state of the world external to a task-performing system, we did an evolutionary simulation study using the simulation framework MABE (Bohm, Lalejini, Schossau & Ofria, 2019). This framework, and the particular settings and environment implemented, have been used to study IIT in an evolutionary context before (Juel, Comolatti, Tononi & Albantakis, 2019). We attempted to replicate parts of the results from Albantakis et al (2014) where it was found that animats (artificial adaptive agents) on average evolved more concepts and higher values of Φ when the task environment was harder and more complex compared to when it was simpler.…”
Section: Methodsmentioning
confidence: 99%